Fragmented Care is Prevalent Among Inflammatory Bowel Disease Readmissions and is Associated With Worse Outcomes. (February 2019) - Cohen-Mekelburg, Shirley; Rosenblatt, Russell; Gold, Stephanie; Shen, Nicole; Fortune, Brett; Waljee, Akbar K.; Saini, Sameer; Scherl, Ellen; Burakoff, Robert; Unruh, Mark
Abstract : OBJECTIVES: Inflammatory bowel disease (IBD) is a complex chronic disease that often requires a multispeciality approach; thus, IBD patients are prone to care fragmentation. We aim to determine the prevalence of fragmentation among hospitalized IBD patients and identify associated predictors and visit-level outcomes. METHODS: The State Inpatient Databases for New York and Florida were used to identify 90-day readmissions among IBD inpatients from 2009 to 2013. The prevalence of fragmentation, defined as a readmission to a non-index hospital, was reported. Characteristics associated with fragmented care were identified using multivariable logistic regression. Multivariable models were utilized to determine the association between fragmentation and outcomes (in-hospital mortality, readmission length of stay, and inpatient colonoscopy). RESULTS: Among IBD inpatients, 25, 241 and 29, 033 90-day readmission visits were identified, in New York and Florida, respectively. The prevalence of fragmentation was 26.4% in New York and 32.5% in Florida. Younger age, a non-emergent admission type, public payer or uninsured status, mood disorder, and substance abuse were associated with fragmented care, while female gender and a primary diagnosis of an IBD-related complication had an inverse association. Fragmented inpatient care is associated with a higher likelihood of in-hospital death, higher rates of inpatient colonoscopy, and a longer readmission length of stay. CONCLUSIONS: Over one in four IBD inpatient readmissions are fragmented. Disparities and differences in fragmentation exist and contribute to poor patient outcomes. Additional efforts targeting fragmentation should be made to better coordinate IBD management, reduce healthcare gaps, and promote high-value care.